1986
DOI: 10.1161/01.hyp.8.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Use of the converting enzyme inhibitor enalapril in renovascular hypertension. Effect on blood pressure, renal function, and the renin-angiotensin-aldosterone system.

Abstract: Thirteen patients were entered into a protocol to assess the safety and efficacy of enalapril (MK 421), 5 to 20 mg b.i.d., and hydrochlorothiazide, 50 to 100 mg daily, for the treatment of renovascular hypertension. Specifically monitored were the effects of therapy on blood pressure and pulse, renal function, and the renln-angiotensin-aldosterone axis. Enalapril and hydrochlorothia-zide therapy produced excellent control of blood pressure with no adverse side effects. After approximately 8 weeks of therapy, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…A fall in plasma A11 concentrations might be expected to result from decreased A1 to A11 conversion in circulating blood consequent upon decreased serum free ACE after enalapril treatment. That such a fall was not observed in this study, nor in some others (Reams et al 1986;Mento & Wilkes 1987), has been attributed to direct and negative feedback effects of ACE inhibition. Administration of captopril, another ACE inhibitor, has been shown to increase renin mRNA in kidney (Iwai et al 1988) which, together with the removal of the inhibitory effect of A11 on renin release, results in increases in plasma renin and A1 concentrations.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…A fall in plasma A11 concentrations might be expected to result from decreased A1 to A11 conversion in circulating blood consequent upon decreased serum free ACE after enalapril treatment. That such a fall was not observed in this study, nor in some others (Reams et al 1986;Mento & Wilkes 1987), has been attributed to direct and negative feedback effects of ACE inhibition. Administration of captopril, another ACE inhibitor, has been shown to increase renin mRNA in kidney (Iwai et al 1988) which, together with the removal of the inhibitory effect of A11 on renin release, results in increases in plasma renin and A1 concentrations.…”
Section: Discussioncontrasting
confidence: 68%
“…Acute administration of enalapril causes falls in plasma angiotensin 11 (AII) and aldosterone concentrations, and increases in plasma renin activity (PRA) and angiotensin I (AI) concentration (Hodsman et al 1984). However, chronic administration in humans has been reported to cause no sustained suppression of plasma A11 or aldosterone concentration (Reams et al 1986); in the rat, plasma A11 may increase above normal during chronic enalapril treatment (Mento & Wilkes 1987 lack of continued A11 suppression is induction of ACE production. Studies in the rat have shown that lisinopril administered orally for 2 weeks decreased free ACE in plasma and several tissues, but increased total ACE in plasma and lung (Kohzuki ef al.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings have also been reported in smaller studies of nondiabetic patients with hyperten sion [7,8],…”
Section: Introductionsupporting
confidence: 81%
“…Drugs that block the RAAS reduce intraglomerular pressure which, in turn, leads to a rise in serum creatinine of up to 30% which then stabilizes (110). Although these drugs can be used safely in people with ischemic nephropathy, these people may have an even larger rise in serum creatinine when these drugs are used (111)(112)(113). In the case of severe renal artery stenosis that is bilateral (or unilateral in a person with a single functioning kidney), RAAS blockade can precipitate renal failure.…”
Section: The Safe Use Of Raas Blockers [Aceis Arbs Aldosterone Antamentioning
confidence: 99%